Via de parto e os impactos no aleitamento materno - Vasconcelos, Julia Melo [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Breast milk is essential not only for the immediate nutrition of a newborn, but it is also important in the long term for the mother-baby dyad. This study aimed to investigate the relationship between the duration of breastfeeding, sociodemographic data, and obstetric data with the mode of delivery. This is a cross-sectional study from a Randomized Controlled Clinical Trial entitled "Interventions for the promotion of Self-Efficacy in breastfeeding and the relationship with the duration of Exclusive Breastfeeding," it is a quantitative work with correlation between the variables carried out with 146 postpartum women admitted to the rooming-in unit of the maternity ward of the Hospital das Clínicas of the Botucatu Medical School - UNESP, the larger study was approved by the Research Ethics Committee of the Botucatu Medical School, UNESP, under Opinion number: 5.927.149 and CAAE: 67350123.0.0000.5411. After a period of 120 days, 75 postpartum women reported the status of their breastfeeding. Of these, 40% reported being exclusively breastfeeding, 33.4% were mixed feeding, and 26% reported offering only artificial milk to their children. When analyzing the data, it was identified that the mode of delivery directly impacts skin-to-skin contact at birth and the duration of breastfeeding. However, each breastfeeding experience is unique, so guidance during prenatal care and throughout the postpartum period is important.

O leite materno é essencial não apenas para a nutrição imediata de um recém-nascido, mas também é importante a longo prazo para o binômio mãe-bebê. Este estudo teve como objetivo investigar a relação da duração do aleitamento materno, dados sociodemográficos e dados obstétricos com a via de parto. Este é um estudo é um recorte de um Ensaio Clínico Controlado e Randomizado denominado “Intervenções para a promoção da Autoeficácia em amamentar e a relação com a duração do Aleitamento Materno Exclusivo”, é um trabalho quantitativo com correlação entre as variáveis realizado com 146 puérperas internadas no alojamento conjunto da maternidade do Hospital das Clínicas da Faculdade de Medicina de Botucatu - UNESP, o estudo maior teve sua aprovação do Comitê de Ética em Pesquisa da Faculdade de Medicina de Botucatu, UNESP, sob o número do Parecer: 5.927.149 e CAAE: 67350123.0.0000.5411. Após o período de 120 dias, 75 puérperas informaram a situação na qual se encontrava o aleitamento materno. Destas, 40% relataram estar amamentando exclusivamente, 33,4% em aleitamento misto e 26% referiram estar oferecendo somente leite artificial para seus filhos. Ao analisar os dados, identificou-se que a via de parto impacta diretamente no contato pele a pele ao nascer e na duração do aleitamento materno. Porém, cada experiência de aleitamento é singular, por isso é importante sua orientação durante o pré-natal e ao longo de todo o puerpério.
Delivery method and its impact on breastfeeding
Keywords: Amamentação; Via de parto; Aleitamento materno; Delivery method; Breastfeeding; Health promotion; Nursing; Health education